Inhibition of JAK1/2 Tyrosine Kinases Reduces Neurogenic Heterotopic Ossification After Spinal Cord Injury - Alexander, Kylie A.; Tseng, Hsu-Wen; Fleming, Whitney; Jose, Beulah; Salga, Marjorie; Kulina, Irina; Millard, Susan M.; Pettit, Allison R.; Genêt, François; Levesque, Jean-Pierre (Frontiers in Immunology, 2019)
Neurogenic heterotopic ossifications (NHO) are very incapacitating complications of traumatic brain and spinal cord injuries (SCI) which manifest as abnormal bone tissue formation periarticular muscles. NHO are debilitating as they cause pain, partial or total joint ankylosis and vascular and nerve compression. NHO pathogenesis is unknown and the only effective treatment remains surgical resection, however once resected, NHO can re-occur. To further understand NHO pathogenesis, we developed the first animal model of NHO following SCI in genetically unmodified mice, which mimics most clinical features of NHO in patients. We have previously shown that the combination of 1) a central nervous system lesion (SCI) and 2) muscular damage (via an intramuscular injection of cardiotoxin) is required for NHO development. Furthermore macrophages within the injured muscle play a critical role in driving NHO pathogenesis. More recently we demonstrated that macrophage-derived oncostatin M (OSM) is a key mediator of both human and mouse NHO. We now report that inflammatory monocytes infiltrate the injured muscles of SCI mice developing NHO at significantly higher levels compared to mice without SCI. Muscle infiltrating monocytes and neutrophils expressed OSM whereas mouse muscle satellite and interstitial cell expressed the OSM receptor (OSMR). In vitro recombinant mouse OSM induced tyrosine phosphorylation of the transcription factor STAT3, a downstream target of OSMR:gp130 signaling in muscle progenitor cells. As STAT3 is tyrosine phosphorylated by JAK1/2 tyrosine kinases downstream of OSMR:gp130, we demonstrated that the JAK1/2 tyrosine kinase inhibitor ruxolitinib blocked OSM driven STAT3 tyrosine phosphorylation in mouse muscle progenitor cells. We further demonstrated in vivo that STAT3 tyrosine phosphorylation was not only significantly higher but persisted longer in injured muscles of SCI mice developing NHO compared to mice with muscle injury without SCI. Finally, administration of ruxolitinib for 7 days post-injury significantly reduced STAT3 phosphorylation in injured muscles in vivo as well as NHO volume at all analyzed time-points up to 21 days post-surgery. Our results indentify JAK/STAT3 signaling pathway may be a potential therapeutic target to reduce NHO development following SCI.